PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Natsir, Irmawaty; Taufik, Abdul Rachman (Jurnal Pendidikan Matematika (JUPITEK), 2020)
This research discusses several problems found in the field, studying the learning process that is still dominated by the teacher, avoiding student participation in active learning activities, increasing student motivation in learning, and increasing collaboration between students. This research was conducted in one of the State Junior High Schools located in Makassar City, Indonesia in the academic year 2017/2018 which aims to improve student learning outcomes through the application of investigative group learning models. The research subjects were students of class VIII with 31 students. This class action research consists of 2 cycles, where each cycle consists of 3 meetings and 1 cycle test. Information related to student activities is collected using observation sheets and information related to student abilities is collected using tests given at the end of the cycle. Obtaining a score for cycle 1 is 70.48 with a completeness level of 70.79% and a score for cycle 2 is 76.32 with a completeness level of 87.1%. After applying learning with the investigation stage the group showed an increase in activity and the ability of students in the second cycle that was supported had reached classical completeness by 75%